SP0020 The Role of Micrornas in The Pathogenesis of Osteoarthritis. (15th July 2016) - Clark, I.; ,
Abstract : Small non-coding RNAs known as microRNAs (miRs) have recently been recognised as important regulators of gene expression in human cells. Whilst originally mooted to fine-tune gene expression, it is now clear that they can have profound effects on physiology and disease. A role for microRNAs in chondrogenesis and osteoarthritis has become clear over the last decade. Deletion of the machinery for microRNA biogenesis specifically in the cartilage of mice has shown that, as a class, microRNAs influence the development of the skeleton and homeostasis of articular cartilage. Identifying roles for individual microRNAs has been more difficult, with the main in vivo data coming from miR-140. This session will review the role of microRNAs in the molecular pathogenesis of osteoarthritis (OA). It will present data on the regulation of microRNAs by relevant factors and their impact on intracellular signalling. Key targets of microRNAs in OA will also be explored. It will touch upon the use of microRNAs as circulating biomarkers of disease and the potential for microRNA-based therapy. The focus of the Clark lab has been on the role and function of microRNAs in cartilage, particularly miR-455, the miR-29 family, miR-140 and miR-3085. MicroRNA-455 is genomically located within an intron of COL27A1. Collagen XXVII is expressed in cartilage, suggesting function of the miR in this tissue. We initially described a role for miR-455 in TGFbeta signalling, but have more recently uncovered function in Wnt signalling and in the regulation of Sirt1. The miR-29 family have been well-researched and are known e.g. to regulate collagen gene expression, giving them a role in fibroses. We identified miR-29b as one of only two miRs which was regulated at an early time point after surgery in the murine DMM ("destabilisation of the medial meniscus") model of OA. Potential targets of miR-29 were regulated in the opposite direction to the miR, suggesting function. The miR-29 family were regulated in many models of chondrocyte differentiation and in human end-stage OA. In chondrocytes we have shown that miR-29 is negatively regulated by Sox9 and negatively regulates a number of key intracellular signalling pathways in OA. We have identified novel direct targets in the Wnt pathway and we have also shown that miR-29 directly targets a number of ADAMTS protease genes. We used RNA-Seq to explore the full range of miRs expressed by human articular chondrocytes from OA patients. This showed that the so-called passenger strand of miR-140, miR-140-3p was more highly expressed than the guide strand, miR-140-5p in newly isolated osteoarthritic chondrocytes. We have now shown that miR-140-3p directly targets a number of enzymes in the heparan sulphate proteoglycan synthesis pathway. These studies also identified miR-3085 in human chondrocytes. This miR had only previously been annotated in rodents where it was presumed intergenic. However, in man it is located in the final intron of the CRTAC1 gene, which codes for cartilage acidic protein 1. We have shown it to directly target ITGA5, the integrin alpha5 gene, but it also strongly induces interleukin-1 signalling in chondrocytes. Disclosure of Interest: None declared